2017
DOI: 10.2215/cjn.00180117
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Mutational Spectrum of Turkish Patients with Cystinosis

Abstract: The most common cystinosis gene mutations identified in Turkey were c.681G>A (p.Glu227Glu), c.1015G>A (p.Gly339Arg), and c.18_21 del (p.Thr7Phefs*7). Patients with less severe cystinosis gene mutations tend to have better kidney outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Indeed, we distinguished three functional groups: those that led to the synthesis of a cystinosin variant with residual cystin efflux activity (RA, residual activity), those that led to the synthesis of an inactive cystinosin variant (IP, inactive protein), and those that did not allow for the protein to be translated and present at the lysosome membrane (AP, absent protein). The justification of mutations classification is proposed in Table 5 [ 2 , 20 , 21 , 22 , 23 , 24 ]. The localization of the different mutations is illustrated in Figure 2 [ 1 , 2 , 20 , 23 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we distinguished three functional groups: those that led to the synthesis of a cystinosin variant with residual cystin efflux activity (RA, residual activity), those that led to the synthesis of an inactive cystinosin variant (IP, inactive protein), and those that did not allow for the protein to be translated and present at the lysosome membrane (AP, absent protein). The justification of mutations classification is proposed in Table 5 [ 2 , 20 , 21 , 22 , 23 , 24 ]. The localization of the different mutations is illustrated in Figure 2 [ 1 , 2 , 20 , 23 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genotype/phenotype analysis that we propose hinges on the first rational classification of mutations in the CTNS gene and is based on the functional consequences of these mutations on the structure of cystinosin. The justification of mutations classification is based on a multi-disciplinary approach taking into account both published experimental data and patients’ clinical phenotype, with a discussion involving physicians, biochemists, geneticists, and basic scientists [ 2 , 20 , 21 , 22 , 23 ]. In light of the results, this classification appears relevant since it makes it possible to predict a response profile to cysteamine as a function of the patient’s underlying genotype.…”
Section: Discussionmentioning
confidence: 99%
“…1 Percentage of the patients with gastrointestinal complications according to leucocyte cystine level registry and confirmed that none of the patients had thee 57-kb CTNS deletion. In that study, the most common alleles in Turkey is c.681G.A (p.E227E; 31%), c.1015G.A (p.Gly339Arg; 22%) and c.18_21 del (p.Thr7Phefs*7; 14%) [29]. Consistent with this result, in our study, the most common mutation was c.1015G > A [p.Gly339Arg] (20%) followed by c.681G > A [p.Glu227-Glu] (16.7%).…”
Section: Discussionmentioning
confidence: 89%
“…The breakpoints of this 57,257 base pair deletion locate in exon 10 of CTNS and intron 2/3 of TRPV1 , resulting in deletion of large parts of CTNS , all of CARKL/SHPK and the two non-coding exons of TRPV1 (13). However, in other populations, this deletion appears a lot less frequent and previous reports did not identify this allele in cystinosis cases from Middle Eastern countries including Egypt, Iran, Jordan, Turkey, and Saudi Arabia (14).…”
Section: Introductionmentioning
confidence: 79%